Identification of Extracellular d-Catenin Accumulation for Prostate Cancer Detection - Lu, Qun; Zhang, Jiao; Allison, Ron R.; Gay, Hiram A.; Yang, Wan-Xi; Bhowmick, Neil; Frelix, Gloria; Shapell, Scott; Chen, Yan-Hua (East Carolina University, 2009)
BACKGROUND—Prostate cancer is the second leading cause of cancer death in men, and early detection is essential to reduce mortality and increase survival. δ-Catenin is a unique β-catenin superfamily protein primarily expressed in the brain but is upregulated in human prostatic adenocarcinomas. Despite its close correlation with the disease, it is unclear whether δ-catenin presents the potential in prostate cancer screening because it is an intracellular protein. In this study, we investigated the hypothesis of δ-catenin accumulation in the urine of prostate cancer patients and its potential pathways of excretion into extracellular milieu. METHODS—Prostate cancer cell cultures, human tissue biopsies, and voided urines were characterized to determine extracellular δ-catenin accumulation and co-isolation with exosomes/ prostasomes. RESULTS—We identified δ-catenin in culture media and in the stroma of human prostate cancer tissues. In PC-3 cells in culture, δ-catenin was partially co-localized and co-isolated with raftassociated membrane protein caveolin-1 and glycosylphosphatidylinositol-anchored protein CD59, suggesting its potential excretion into extracellular milieu through exosome/prostasome associated pathways. Interference with endocytic pathway using wortmannin did not block prostasome excretion, but δ-catenin overexpression promoted the extracellular accumulation of caveolin-1. δ- Catenin, caveolin-1, and CD59 were all detected in cell-free human voided urine prostasomes. δ- Catenin immunoreactivity was significantly increased in the urine of prostate cancer patients (p<0.0005). CONCLUSIONS—This study demonstrated, for the first time, the extracellular accumulation of δ-catenin in urine supporting its potential utility for non-invasive prostate cancer detection. Originally published The Prostate, Vol. 69, No. 4, March 1 2009
Keywords: Prostate cancer detection; Catenin; Caveolin-1; CD59; Prostate-Specific Antigen